Development of a core outcome set for school-based intervention studies on preventing childhood overweight and obesity: study protocol - Mai Chinapaw; Teatske M Altenburg; Tessa J Roseboom; Jo Salmon; Deirdre Harrington; Lotte W de Vries; Iris Grooten; Janneke Van 't Hooft; Arend van Deutekom (BMJ Open)
Introduction Prevention of childhood overweight is an important health priority. Evidence synthesis from studies evaluating school-based overweight preventive interventions is hampered by the wealth of different outcomes across studies. Therefore, consensus on a core set of outcomes for school-based overweight prevention studies is needed. This paper presents the protocol for the development of a core outcome set (COS) for school-based intervention studies aimed at childhood overweight prevention.Methods and analysis First, a scoping review will be performed to identify outcomes included in studies evaluating school-based overweight prevention interventions in 6–12 year-old children. Additionally, child focus groups will be organised in three countries to list the outcomes children consider important in school-based interventions. Next, an expert panel will identify all unique outcomes (eg, body composition) from the results of the scoping review and focus groups, ruling out how outcomes were defined and measured (eg, body mass index, body fat). In the next phase, a group of international stakeholders will participate in a Delphi study in which they will rate all unique outcomes on a 9-point Likert scale over three rounds to reach consensus on a COS. Participants will include healthcare professionals, policymakers, teachers, school leaders and parents of 6–12 year-olds. All rated outcomes will be presented to stakeholders in two online consensus meetings.Ethics and dissemination The Medical Ethics Committee of the VU Medical Center approved the child focus group study in the Netherlands (nr. 2020.071) and the Delphi study—including the consensus meeting (nr. 2022.0295). Other sites will obtain ethics approval for focus groups in their country. The University of Strathclyde School of Psychological Sciences ethics committee approved the Delphi study—including consensus meeting (nr. 72.27.04.2022 .A). The final COS will be disseminated through the diverse networks of all authors and participants.Trial registration number This COS initiative is registered with the Core Outcome Measures in Effectiveness initiative (registration nr. 971).